CYBERLOAFING SEBAGAI STRATEGI MENGATASI KEBOSANAN KERJA - Siti Nur Azizah; Harini Abrilia Setyawati (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
Cyberloafing has been considered as a form of opposite / unproductive work behavior (CWB) that can endanger organizations. This study takes a different view that cyberloafing can show a potentially positive function in this context that can help employees overcome boredom at work. The sample of this study was 70 administrative employees at junior high schools in Kebumen which were taken randomly. By using PLS assistance we tested the relationship between low work underload on cyberloafing and counter-productive behavior with boredom as mediators. The results of the study indicate boredom mediates the work underload and cyberloafing relationship. Cyberloafing is used by employees as a coping strategy (adaptive behavior) to overcome work boredom compared to counter-productive behavior Keywords: Cyberloafing, work underload, kebosanan, counter productive work behavior(CWB)